Patient care, right to information and consent for minors in situations of parental conflict. Clinical guidelines in the context of Spanish legislation - Laura Pina-Camacho; Jorge Vidal; María Dolores Picouto; Encarna Justo Ortiz; Federico de Montalvo Jääskeläinen; Carmen Moreno; Celso Arango; Teresa Hernández-Sampelayo; Mara Parellada; Carmen Miranda; Constancio Medrano; Jesús López-Herce; et al. (Elsevier, 2021)
Among the main social and legislative changes in Spanish family law in recent years, are (i) the increase of judicialised conflicts between parents and (ii) the enactment of the Spanish Law 26/2015, which amended the Spanish Autonomy Law 41/2002, and sought to balance the rights of minors and parents, especially minors who had not reached 16 years of age or, having reached it, faced decisions that could put their lives or health at serious risk. Likewise, recent jurisprudence has determined that, regardless of minor's age, there are sensitive "extraordinary" or "transcendent" healthcare acts, such as psychotherapeutic or surgical interventions, which require the consent of both parents, with some exceptions. All this, however, is subject to the discretion of the responsible physician, who must always ensure the best interest of the minor. Child health care therefore often raises complex conflicts involving parental rights to information and consent, especially when parental opinions differ. We present a review of the current legislative framework and the most relevant legal concepts that regulate the care of minors with regard to rights to information and minor vs. parental consent. We also present clinical guidelines for caring for minors in situations of parental conflict developed at Gregorio Marañón University Hospital in Madrid, Spain, and endorsed by the Official College of Physicians of Madrid, Spain. Resumen: Entre los principales cambios sociales y legislativos que se han producido en España en los últimos años en materia de familia, se encuentran (i) el aumento progresivo de situaciones de conflicto judicializado entre progenitores y (ii) la aparición de la Ley 26/2015 de Protección a la Infancia, que modificó la Ley 41/2002 de Autonomía del Paciente, y buscó un cierto equilibrio entre los derechos de los menores y las facultades de los progenitores, sobre todo cuando aquéllos no habían alcanzado los 16 años o la suficiente madurez o, habiéndola alcanzado, la decisión ponía en grave riesgo su vida o salud. Asimismo, se ha generado jurisprudencia que determina que, para cualquier menor de edad, existen actos asistenciales especialmente sensibles, "extraordinarios" o "trascendentes", como las intervenciones psicoterapéuticas o las quirúrgicas, las cuales requieren, salvo excepciones, el consentimiento de ambos progenitores para llevarse a cabo. Todo ello, sin embargo, sujeto al criterio del facultativo responsable, quien debe siempre velar por el mejor interés del menor. La asistencia a menores plantea, por ello, en ocasiones, conflictos complejos en materia de información y consentimiento por parte de los progenitores, sobre todo cuando la opinión de estos no es coincidente. Presentamos una revisión del marco legislativo vigente y de los principales conceptos jurídicos que regulan la asistencia a menores en materia de información y consentimiento relativos a la salud, así como un protocolo asistencial para la atención a menores en situaciones de conflicto entre progenitores, desarrollado en el Hospital Gregorio Marañón de Madrid y avalado por el Ilustre Colegio Oficial de Médicos de Madrid.